Maternal exposure to ambient air pollution and risk of congenital heart defects in Suzhou, China - Sun, Li; Wu, Qianlan; Wang, Huiying; Liu, Juning; Shao, Yan; Xu, Rong; Gong, Tian; Peng, Xiaoju; Zhang, Baoli (Frontiers in Public Health, 2023)
Background More and more studies have investigated the association between maternal exposure to ambient air pollution during pregnancy and incidence of congenital heart defects (CHDs), but results are controversial. The aim of this study was to investigate whether maternal exposure to air pollutants (PM10, PM2.5, NO2, CO, SO2) are associated with an increased risk of congenital heart defects in Suzhou city, China. Methods Based on the birth defect monitoring system of Suzhou city and the Environmental Health Department of Suzhou CDC, the birth defect monitoring data and concentrations of five air pollutants (PM10, PM2.5, NO2, CO, SO2) in Suzhou city from 2015 to 2019 were obtained. The distribution of demographic characteristics of children with birth defects and exposure to air pollutant concentrations during different pregnancy periods were analyzed, Chi-square test was used to analyze whether there were statistical differences in the distribution of parturient woman age, pregnant weeks, times of pregnancy, as well as fetal sex and birth weight among children with congenital heart defects and other defects. Logistic regression model was further established to calculate the adjusted odds ratios (aORs) and 95% confidence intervals (CI) for the association between exposure to these ambient air pollutants during pregnancy and CHDs. Results A total of 5,213 infants with birth defects were recruited in this study from 2015 to 2019, the top five birth defects in Suzhou were syndactyly, congenital heart disease, ear malformation, cleft lip and palate, and hypospadias, and the proportion of congenital heart disease increased. The level of maternal exposures (mean ± sd) was highest in first trimester amongst pregnant women in Suzhou city. Compared to other birth defects, we observed significant increasing associations between PM2.5 exposure during second and third trimester with risk of CHDs, aORs were 1.228 and 1.236 (95% CI: 1.141–1.322, 1.154–1.324 separately) per a 10 μg/m3 change in PM2.5 concentration. Maternal NO2 exposure was significantly associated with CHDs in first trimester (aOR = 1.318; 95% CI: 1.210–1.435). Conclusions Our study contributes to explore the current state of Suzhou air quality and the association between maternal air pollution exposure and congenital heart defects. Exposure to PM2.5 and NO2 is thought to increase the risk of CHDs, but comprehensive description of these associations will be needed in future studies.